2018
DOI: 10.1038/s41598-018-35997-x
|View full text |Cite
|
Sign up to set email alerts
|

Ninjurin1 Plays a Crucial Role in Pulmonary Fibrosis by Promoting Interaction between Macrophages and Alveolar Epithelial Cells

Abstract: The transmembrane nerve injury-induced protein 1 (Ninjurin1 or Ninj1) is involved in progressing inflammatory diseases. In this study, we aimed to investigate a novel function of Ninj1 in pulmonary fibrosis. We found that the expression of Ninj1 in a patient cohort was upregulated in the lung specimens of idiopathic pulmonary fibrosis patients as well as mice with bleomycin-induced pulmonary fibrosis. In addition, the BLM-injected Ninj1 KO mice exhibited a mild fibrotic phenotype, as compared to WT mice. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Macrophage infiltration is shown to be crucial for regulating the progression of lung fibrosis [6,7]. However, in the study of lung fibrosis and Ninj1, we demonstrated similar numbers of infiltrating macrophages in bronchoalveolar lavage fluids of bleomycin-treated WT and Ninj1 KO mice for lung fibrosis, indicating that macrophage infiltration does not determine the phenotypic difference between bleomycin-treated WT and Ninj1 KO mice [5].…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…Macrophage infiltration is shown to be crucial for regulating the progression of lung fibrosis [6,7]. However, in the study of lung fibrosis and Ninj1, we demonstrated similar numbers of infiltrating macrophages in bronchoalveolar lavage fluids of bleomycin-treated WT and Ninj1 KO mice for lung fibrosis, indicating that macrophage infiltration does not determine the phenotypic difference between bleomycin-treated WT and Ninj1 KO mice [5].…”
Section: Introductionmentioning
confidence: 55%
“…Thus, it was surprising that during colitis development, Ninj1 did not alter the migration capacity of macrophages, which is seen only in lung fibrosis. Upon bleomycin treatment, Ninj1 KO mice ameliorated lung fibrosis; however, the number of infiltrating macrophages from both KO and WT mice were not different [5]. During development of colitis and lung fibrosis, the Ninj1 pathway controlled activation of the macrophages, resulting in the triggering an inflammatory response.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations